A Fool's Errand? The Next Secretary‐General and United Nations Reform. Issue 2 (2nd May 2017) - Ponzio, Richard; Bluman Schroeder, Michael
Abstract: How can the incoming Secretary‐General António Guterres promote and lead change? The view in many policy circles is that the UN urgently needs comprehensive change, and the next Secretary‐General is expected to capitalize on the honeymoon to initiate a transformation. We argue that initiating transformational change is counterproductive for the next Secretary‐General. A better strategy is to implement modest changes that accumulate over multiple rounds and to influence and empower the leadership of so‐called 'smart coalitions' of state and non‐state actors seeking to enact ambitious changes to intergovernmental structures and global norms. Specifically, we propose a change leadership strategy for the next Secretary‐General based on five guiding principles and including illustrative reforms that suggest how the next Secretary‐General might put each principle into practice. Abstract : Secretary‐General Guterres will need to balance humility and ambition as he is unlikely to be able to take credit for leading the most dramatic changes—even as he plays a crucial role in facilitating them.